Bioremediation of Polycyclic Aromatic Hydrocarbons in Contaminated Soils Using Vermicompost - Fazel Mohammadi-Moghadam; Ramazan Khodadadi; Morteza Sedehi; Mohsen Arbabi (International Journal of Chemical Engineering)
Bioremediation of polycyclic aromatic hydrocarbons (PAHs) in contaminated soils are reported in many literatures. Composting, in addition to bioremediation, can simultaneously increase soil organic matter content and soil fertility and is thus regarded as one of the most cost-effective methods of soil remediation. In this study, biodegradation of phenanthrene (PHE) and pyrene (PYR) is reported by microbial consortia enriched by vermicompost. After soil samples preparation and grinding, the samples were contaminated with 100, 200, and 300 mg/kg of PHE and PYR concentrations and inoculated with three concentrations (2, 4, and 6 wt.%) of vermicompost. PHE and PYR concentrations were analyzed by HPLC during bioremediation. After 70 days, two highly capable microbial consortia were used to remove the pollutants in bioaugmentation conditions. Analysis of their microbial composition revealed that the consortia contain several Proteobacteria phylum bacterial species, and the most common genera were Pseudomonas and Citrobacter. Decontamination rates for PHE and PYR were estimated to be 89% and 83% over 45 days, respectively. Biodegradation kinetics revealed that microbial degradation followed a first-order kinetics. This study provides clear evidence on the biodegradation of PHE and PYR, paving the way for the development of bioremediation technologies for the recovery of polluted ecosystems.